1980
DOI: 10.1177/000348948008900318
|View full text |Cite
|
Sign up to set email alerts
|

Sphenooccipital Chordoma Presenting as a Nasopharyngeal Mass

Abstract: While the nasopharynx is most commonly regarded by the otolaryngologist as a primary site of neoplastic involvement, it is also an avenue of spread of base-of-the-skull tumors presenting as bulging nasopharyngeal masses. The temporal sequence of clinical signs and symptoms may reliably predict the origin of a ventrally extending sphenooccipital chordoma seen on a nasopharyngeal examination. This tumor may cause extensive bony erosion of the petrous apex, sphenoid sinus, and clivus and may suggest a more rapidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…In the absence of the mass in FOR but with strong clinical suspicious of NPC, the radiological imaging such as computed tomography scan or magnetic resonance (MR) imaging is valuable to pick up the sub-mucosal type of NPC. [3] In areas of NPC endemics, for example China, the use of MR imaging as a screening…”
Section: Commentarymentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of the mass in FOR but with strong clinical suspicious of NPC, the radiological imaging such as computed tomography scan or magnetic resonance (MR) imaging is valuable to pick up the sub-mucosal type of NPC. [3] In areas of NPC endemics, for example China, the use of MR imaging as a screening…”
Section: Commentarymentioning
confidence: 99%
“…The extent of the tumor may be accurately determined by conventional tomography, computerized axial tomography, and arteriography. [3] Most are treated with radiotherapy (RT) because of extensive involvement making them unresectable. Because of the risk of severe late complications, the dose is often limited with conventional photon RT, and the probability of cure is low.…”
Section: Introductionmentioning
confidence: 99%
“…The sacrum is the commonest site followed by the base of the skull/clival region. Spheno-occipital chordomas giving rise to the formation of a nasopharyngeal mass have been described in literature [1]- [3]. When skull base chordomas occur at an extraosseous location (without lytic bone destruction), they may mimic other lesions of the nasopharynx.…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators reported the difficulty of predicting distant metastasis on the basis of histological findings [4,9,18,25,35,36], although Chambers and Schwinn suggested a relationship between the metastasis and anaplastic histological features such as pleomorphism and hyperchromatism [5], which are known to be common in chordomas [5,10,26,30]. Many studies suggested the proliferative potentials of neoplasms to be essential for evaluating their biological features [8, 14, 19-22, 24, 29], and thus, the proliferative potentials of chordomas should be elucidated with reference to the clinical course including tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%